Kerangka penghasilan parameter penilaian selepas dihuni di bangunan pejabat kerajaan - Bakar, Norazmi (2009)
Post-Occupancy Evaluation (POE) is one of the elements in Building Performance Evaluation (BPE) process. The purpose is to evaluate the building performance in a systematic manner after it has been built and occupied for some time. The implementation of POE is to measure occupants’ satisfaction and comfortable level of the building and facilities provided. It is an important input for the architect and facilities manager to integrate the building and its facilities to meet the occupants’ needs. Steps in POE required some modification to meet socialculture needs. POE approach in architecture and facilities management are slight different. The objective of this research is to identify parameters in POE and serve as a basis for questionnaire design during implementation the POE. Quantitative technique aided with computer software has been used extensively to analyze all the data obtained. The office buildings at Jabatan Kerja Raya Headquarters were selected as a case study and sample selected randomly from the staff who occupied the buildings. Findings from the research indicates that almost all the surveyed parameters were relevance to the respondents. Researcher proposed other ways to be used to obtain new parameter.